Patient doses in chest CT examinations: Comparison of various CT scanners - Božović Predrag; Ciraj-Bjelac Olivera; Aranđić Danijela; Hadnađev Darka; Stojanović Sanja (Serbian Journal of Electrical Engineering, 2013)
This paper presents results from study on patient exposure level in chest CT examinations. CT scanners used in this study were various Siemens and General Electric (GE) models. Data on patient doses were collected for adult and pediatric patients. Doses measured for adult patients were lower then those determined as Diagnostic Reference Levels (DRL) for Europe, while doses for pediatric patients were similar to those found in published data. As for the manufactures, slightly higher doses were measured on GE devices, both for adult and pediatric patients.